2006
DOI: 10.1227/01.neu.0000199157.21444.bf
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Extruded Screw Removal after Anterior Cervical Disc Fusion: Technical Case Report

Abstract: A transpharyngeal endoscopic approach to remove loose anterior cervical hardware is feasible and warrants further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Martínez-Lage et al reported that graft dislodgement occurred in 6%–10% of patients, while Lowery and McDonough showed the incidence of instrumentation failure to be as high as 35% [8]. In addition, Lee et al reported 2%–35% plate-related failure in anterior cervical fusions in their literature review [9]. The main predisposing factor to the development of screw and plate extrusion is suboptimal positioning of these screws [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Martínez-Lage et al reported that graft dislodgement occurred in 6%–10% of patients, while Lowery and McDonough showed the incidence of instrumentation failure to be as high as 35% [8]. In addition, Lee et al reported 2%–35% plate-related failure in anterior cervical fusions in their literature review [9]. The main predisposing factor to the development of screw and plate extrusion is suboptimal positioning of these screws [10].…”
Section: Discussionmentioning
confidence: 99%
“…Geyer and Foy reported a 76-year-old woman with oral extrusion of a missing locking plate 5 years after a C4-C5 decompression and fusion [4]. Lee et al demonstrated endoscopic extrusion of a screw after anterior cervical disc fusion, which caused esophageal perforation [9]. Yee and Terry reported a patient with complete screw migration that perforated the esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…Early mobilization is directly related to a deficient fixation technique or other complications, such as hematomas, whereas late migration is frequently related to erroneous placement during surgery …”
Section: Discussionmentioning
confidence: 99%
“…Anterior cervical fixation through different devices has been used for multiple pathologies, such as traumatism, compressive myelopathy, or spinal infections since 1967. [1][2][3][4][5][6][7][8][9] It is a broadly developed technique in neurosurgery with a reported complication rate of 5%-35%. 1 Clinical evolution is usually satisfactory and well tolerated, although serious complications can occur, such as mediastinitis, severe hemorrhage, or epidural abscess.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation